PENGARUH KOMBINASI PAKAN BUATAN DAN PAKAN ALAMI CACING SUTERA (Tubifex tubifex) DENGAN PERSENTASE YANG BERBEDA TERHADAP RETENSI PROTEIN, LEMAK DAN ENERGI PADA IKAN SIDAT (Anguilla bicolor) - Sri Subekti; Mutia Prawesti; Muhammad Arief (Jurnal Kelautan, 2011)
Indonesian short fin eel (Anguilla bicolor) was one of Indonesian fishery commodities which have high value not only in local market but also western market. Advantages of Indonesian short fin eel not only their high value because of prospectively in international market, but also the quality of  Indonesian short fin eel itself that contain high vitamin and micronutrient. Weaknesses of Indonesian short fin eel was their growth classified slow. That was can be overcome by giving the exact feed. The purpose of this research was to know the effect of combination between artificial feed and natural feed with different percentage to protein retention, fat retention and energy retention of Indonesian short fin eel (Anguilla bicolor). This research used experimental method and Completely Random Design method with five treatments. Each treatment was replicated four times. The treatment used were : 100% of artificial feed (A), 75% of artificial feed and 25% of natural feed (B), 50% of artificial feed and 50% of natural feed (C), 25% of artificial feed and 75% natural feed (D), and 100% natural feed (E). The main parameters measured were protein, fat, and energy retentions. The supporting parameters observed was growth rate and water quality. Data analysis used analysis of variance (ANOVA) to know the effect of the treatments. The  difference among treatments were known by using Duncan’s Multiple Range Test (DMRT).The result showed that combination between artificial  and natural feeds with difference percentage showed different effect (p0,05) to fat retention of Indonesian short fin eel therefore they didn’t showed different effect to protein and energy retentions of Indonesian short fin eel (p0,05). Water quality of Indonesian short fin eel rearing medium was 28-31oC in temperatures, 7-8,5 in pH, 3,5-5,8 mg/l in dissolved oxygen and 0,003 mg/l in ammonia. Keywords : Anguilla bicolor, artificial feed, Tubifex tubifex, protein retention, fat retention, energy retention.